PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DISERTAI HANDOUT TERHADAP HSIL BELAJAR BIOLOGI SISWA KELAS X SMAN 1 SUTERA KABUPATEN PESISIR SELATAN - Oktarina, Widia Nofri (Pendidikan Biologi, 2014)
This research is motivated by the low learning outcomes biology student at SMAN 1 Sutera Kabupaten Pesisir Selatan. This is caused by several factors, including applied learning models teachers do not vary, discussions are not heterogeneous and used books limited to less support teaching and learning process. One way to improve learning outcomes is to use STAD cooperative learning model along with handouts on learning outcomes biology class X students of SMAN 1 Sutera. This type of research is experimental. The study design randomized control group only desaign with a population of tenth graders of SMAN 1 Sutera Kabupaten Pesisir Selatan which consists of 8 classes. Sampling technique was done by purposive sampling so that the class as a class experiment X.2 and X.3 as the control class. The research instrument used was the ultimate test of learning outcomes in the form of an objective test. Data analysis was performed by t test. Based on the results of biological study gained an average student learning outcomes experimental class (62.37), higher when compared to the control group (58.59). From the analysis of the data obtained t was 1,320 while 1,676 TTable. Because tcalculation <ttable then the hypothesis is rejected. It can be concluded that there is no Influence Application Type STAD Cooperative Learning Model with Learning Outcomes Against Handouts Biology Class X SMAN 1 Sutera Kabupaten Pesisir Selatan.